Calculating Selfishness: A reading of Deleuze and Guattari’s concept of the plane of nature - Wisniowska, Magdalena (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
This essay offers a reading of Deleuze and Guattari’s concept of the plane of nature, as presented in A Thousand Plateaus. It uses their definition of this plane as an abstract machine of an infinity of particles and their infinity of interconnected relations to address the challenge of the machine thesis identified by Arjen Kleinherenbrink: of how to think world consisting only of machines yet allowing for interaction and change. Referencing Spinoza and the calculus inherent in Deleuze’s earlier work, it offers an interpretation of a discontinous virtual.